2020
DOI: 10.1002/ctm2.228
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic DNA‐STING‐NLRP3 axis is involved in murine acute lung injury induced by lipopolysaccharide

Abstract: 1. Cytosolic DNA-STING-NLRP3 axis contributes to LPS-induced acute lung injury. 2. TLR4 isessential for the activation of cGAS-STING pathway in macrophages stimulated by LPS. 3. LPS stimulation couldenhance the transcriptional activation of STING via c-Mycinmacrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 47 publications
2
125
0
Order By: Relevance
“… 28 We recently reported that NLRP3 inflammasome-dependent macrophage pyroptosis may also contribute to lung injury caused by sepsis. 6 Hence, inflammasome inhibition may serve as a pharmacological target for relieving ALI induced by infection or trauma. In this study, we reported that NLRP3 inflammasome and pyroptosis could be inhibited by MF in LPS-treated lung tissues and macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 We recently reported that NLRP3 inflammasome-dependent macrophage pyroptosis may also contribute to lung injury caused by sepsis. 6 Hence, inflammasome inhibition may serve as a pharmacological target for relieving ALI induced by infection or trauma. In this study, we reported that NLRP3 inflammasome and pyroptosis could be inhibited by MF in LPS-treated lung tissues and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…All experimental animal in our study were fed in a specific-pathogen-free (SPF) environment (humidity 50 ± 3%, temperature 22–25◦C). As described previously, 6 to establish the murine ALI model, LPS was dissolved in 50 μL sterile saline and instilled intratracheally at a dose of 5 mg/kg. An isovolumetric sterile saline was instilled intratracheally in mice from the control group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to intracellular cytosolic "self-DNA," exosome secretory and circulatory cell-free mtDNA are also suggested to contribute to AIM2 inflammasome-mediated inflammation [57]. have been shown to be associated in multiple sets, such as acute lung injury [58] and age-related liver ischemiareperfusion injury (IRI) [59]. Typically, the stimulated cGAS-STING axis initiates inflammasome assembly and activation via type-I IFN signaling [60,61] or K+ efflux induced by the translocation of STING to the lysosome and the subsequent lysosomal rupture [62].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Western blot was performed as our previously described 17 . Extracting the total proteins of fresh ventricle tissues or iced cell lysates and quanti ed, approximately 50 µg of total proteins were loaded on an SDS/PAGE gel.…”
Section: Western Blot and Real-time Pcrmentioning
confidence: 99%